Institutional Quality and Economic Growth in Africa: The Moderating Role of Financial Inclusion and Literacy - Nambie, Nicholas Bamegne; Ocansey, Evans O. N. D.; Ababio, Opoku (International Journal of Economics and Financial Issues, 2025)
Correlation between institutional quality and economic growth in Africa, with particular emphasis on the moderating influences of financial inclusion and literacy was examined to investigate the degree to which financial inclusion and literacy contribute to the efficacy of institutional quality in promoting economic development. The research encompasses a total of 42 African nations, covering the timeframe from 2003 to 2024, and offers an extensive examination of the interrelations among these significant variables. The research employs panel data obtained from esteemed international databases, such as the World Bank and various regional economic reports, thereby ensuring the reliability and robustness of the results. To conduct the analysis of the data, dynamic panel estimation techniques are utilized, particularly the System Generalized Method of Moments (GMM). This approach effectively resolves endogeneity concerns and encapsulates the dynamic characteristics of economic growth. The findings indicate that institutional quality exerts a substantial influence on economic growth; however, this effect is magnified when it is associated with elevated levels of financial inclusion and literacy. These findings emphasize the significance of implementing a multi-faceted approach to development, which combines institutional reforms with initiatives aimed at improving financial inclusion and educational outcomes. This research enhances the existing body of literature by presenting empirical evidence regarding the interactive effects of institutional quality, financial inclusion, and literacy. It offers significant insights for policymakers and development practitioners operating within the African context.